Changes in the Gut Microbiota May Affect the Clinical Efficacy of Oral Anticoagulants - Wenjun Chen; Wenjun Chen; Jiafen Qian; Jiafen Qian; Jinglan Fu; Jinglan Fu; Tingting Wu; Tingting Wu; Meina Lv; Meina Lv; Shaojun Jiang; Shaojun Jiang; et al. (Frontiers Media S.A., 2022)
The mechanism underlying large individual differences in the response to oral anticoagulants has not been fully clarified, and the influence of the intestinal microbiome on exogenous drug metabolism has gradually become an area of increased research interest. However, there has been no research into the influence of the gut microbiota on the pharmacokinetics of oral anticoagulants. Therefore, our study is the first to investigate the effect of the intestinal flora on oral anticoagulant metabolism and the associated mechanism. Antibiotics affected the diversity and abundance of the intestinal flora. Compared with the control group, the bioavailability of warfarin and rivaroxaban were significantly increased in the amoxicillin-treated group, whereas the bioavailability of dabigatran increased and subsequently decreased. Compared with the control group, the expression of P-glycoprotein (P-gp), CYP1A2, CYP2C9, CYP3A4, and nuclear receptor, PXR, were altered in the amoxicillin -treated groups. This trend was consistent with the pharmacokinetic results. Changes in the intestinal flora can affect the expression of liver drug enzymes and P-gp, as well as affect the transport and metabolism of oral anticoagulants (e.g., warfarin, dabigatracin, and rivaroxaban), leading to differences in the efficacy of oral anticoagulants. This study revealed a novel mechanism for influencing individual differences in the treatment efficacy of oral anticoagulants.